Convexidade generalizada em problemas de controle ótimo com tempo livre - Villanueva, Fabiola Roxana [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In this work we study necessary and sufficient optimality conditions for free end-time optimal control problems, comprising the study of the Maximum Principle and generalized convexity. We introduce the necessary conditions of the xed end-time maximum principle and of the free end-time maximum principle. Next, we present sufficient conditions for xed end-time optimal control problems; we introduce two de nitions of generalized con- vexity, the rst called LMP-pseudoinvexity, which involves the Lagrange multipliers and the second called MP-pseudoinvexity, which does not involve the Lagrange multipliers. We show that for a LMP-pseudoinvex problem all the MP-processes (control processes that satisfy the necessary conditions of the maximum principle) are optimal processes and con- versely the problems such that all the MP-processes are optimal, are LMP-pseudoinvex problems; also we show that under some conditions, LMP-pseudoinvexity is equivalent to MP-pseudoinvexity. Finally, we present sufficient conditions for free end-time optimal control problem; we introduce a de nition of generalized convexity called MP-free pseudoinvexity, which does not involve the Lagrange multipliers. We show that under some conditions, if the problem is MP-free pseudoinvex, then all normal MP-processes are optimal; also we show that under some conditions, if the problem is such that every MP-process is an optimal process, then the problem is MP-free pseudoinvex

Neste trabalho estudamos condicões necessárias e suficientes de otimalidade para problemas de controle ótimo com tempos finais livres, compreendendo o estudo do Princípio do Máximo e convexidade generalizada. Apresentamos as condições necessárias do princípio do máximo com tempos finais fixos e do princípio do máximo com tempos finais livres. Logo apresentamos as condições suficientes para problemas de controle ótimo com tempos finais fixos; introduzimos duas definições de convexidade generalizada, a primeira denominada PML-pseudoinvexidade, que envolve os multiplicadores de Lagrange e, a segunda denominada PM-pseudoinvexidade, que não envolve os multiplicadores de Lagrange. Mostramos que para um problema PML-pseudoinvexo todos os PM-processos (processos de controle que satisfazem as condições necessárias do princípio do máximo) são processos ótimos e reciprocamente os problemas tais que todos os PM-processos são ótimos, são problemas PML-pseudoinvexos; também mostramos que sob algumas condições, PML-pseudoinvexidade e equivalente a PM-pseudoinvexidade. Finalmente apresentamos as condições suficientes para problemas de controle ótimo com tempos finais livres; introduzimos uma de de nição de convexidade generalizada denominada PM-pseudoinvexidade livre, que não envolve os multiplicadores de Lagrange. Mostramos que sob algumas condições, se o problema e PM-pseudoinvexo livre, então todo PM-processo normal e um processo ótimo; também mostramos que sob algumas condições, se o problema e tal que todo PM-processo e um processo ótimo, então o problema e PM-pseudoinvexo livre
Keywords: Matemática; Teoria do controle; Otimização matematica; Otimização não diferenciável